Engineering Principles and Practices in Dry Land Agriculture - Singh, L.P.; Ram, R.S. (Journal of Soil and Water Conservation, 2022)
Land and water must be managed in a way that will maintain or increase their productivity if our increasing population is to remain relatively self-sufficient in food supplies. Water and soil of any nation are the most valuable resources. In order to grow crops successfully the supply of water should be adequate and timely. It is quite unfortunate that about 55 percent of the land area of the earth receives less than 50 cm of annual rainfall and in the other 20 per cent of the area too, rainfall is not more than 100 cm. These figures show that water deficiency is a problem over atleast 75 percent land area of the world. The total area of arid and semiarid zones in India is 317,090 square Kilometer and 956,750 square Kilometer respectively excluding the cold desert of Jammu and Kashmir State which contains 70,300 square Kilometer of arid and 13,780 square Kilometer of semi-arid land.